DYNAMICS OF THE DEVELOPMENT OF THE MAMLUK DYNASTY IN THE HISTORY OF ISLAMIC CIVILIZATION - Emilia Yurila Waruwu (CV. Fahr Publishing, 2024)
The development of the Mamluk dynasty is not widely highlighted in the study of Islamic history, even though this dynasty played a role in Islamic historical civilization. This makes it urgent to carry out further research aimed at uncovering the development of the Mamluk Dynasty. This research method is descriptive qualitative research using literature study techniques. The findings show that in the development of the Mamluk Dynasty there were two main periods, namely the Mamluk Bahri and Mamluk Burji periods. Factors that supported the rise of the Mamluk dynasty were the ability to withstand attacks by Hulugu troops and the Crusaders, utilizing geographical factors to engage in international trade, and establishing good relations with European countries to increase wealth and reputation. Factors that caused the collapse of the Mamluk dynasty were internal conflicts such as competition for power, instability in government policies, economic problems such as corruption, economic crises and inflation. The weakening of the Mamluk Dynasty's power resulted in the loss of its territory so that it was controlled by the Ottoman Empire. In this case, the existence of the Mamluk dynasty is known to have had a significant impact on Islamic historical civilization, namely being the only dynasty that maintained Islamic culture when the Arabs declined and supported the progress of Islamic science. It is hoped that these findings can increase insight and understanding that the Mamluk Dynasty also played an important role in the history of Islamic civilization.